Análise descritiva da tradução para o inglês da obra Mission Terminée, de Mongo Beti - Elono, Edith Estelle Blanche Owono (2019)
This master thesis analyzes English translation of the work Mission Terminée, first published in 1956 by the Cameroonian writer Mongo Beti (1932-2001). Translated into English in 1958 by the British translator Peter Green, the book was published in England under the title Mission to Kala and in the United States of America as, Mission Accomplished within the same year. This research is based on the 2008 edition, published by Mallory International (London) in its book collection known as the Classic African Writing collection. The analysis uses Descriptive Translation studies (DTS), focusing on the theory of José Lambert and Hendrik Van Gorp (1985), which presents a four level model for analysis of translations. According to the authors, it is a model that has four levels: the preliminary data collection, the macrostructure level, the microstructure level and finally the systemic context level. It is from these levels that we describe, observe and analyze the translation of the book Mission to Kala, comparing it with the source text not to present a judgment on both texts, but in order to come closer to understanding the decisions made by the translator. From this, the choices he made in his recreation task are then studied according to the perspectives of Haroldo de Campos (2009) and Paulo Henriques Britto (1999), complemented by the rewriting and textual manipulation approach by André Leverere (2007). Other studies, such as those by Gérard Genette (2009) and Marie-Hélène Catherine Torres (2011), are also used for the discussion on the presentation of the paratext. Regarding African literature and research on the author's life, the following authors were considered: Ait-T-Aarab (2012), Habiballah (2009), Mokam (2009), Bishop (1988) Djiik (2011) and Senghor (1967). From the analysis of this study, it was found that there many changes in the book in terms of word meanings, punctuation, the use of extensive explanations (many words) that do not add in any way the meaning of the sentence. There were also some problematic choices that give a misleading image of the source text culture. With this, we understand that textual recreation through translation offers the target reader the opportunity to create new meanings around the book. Recreation also presents the translator as a new member of the source culture for having, successfully, penetrates the intimacy of that culture while maintaining his own cultural individuality.